Exploring divisions What to be learned from observing young children's social preferences. Issue 3 (3rd July 2021) - Gulløv, Eva
ABSTRACT: This article concerns young children's social preferences in early childcare in Denmark. Based on detailed and long-term ethnographic observations, the analysis shows how children's choices of playmates are patterned in ways that reflect their various social and cultural experiences in and out of the institutional settings. In general, children seem to prefer to be with others who share and acknowledge the same kinds of knowledge, experiences, and references and this leads to a pattern of rather distinct social interest-groups. The article explores why such lines of divisions are to be found in an institutional context designed to overcome social inequality and prevent social fragmentation. Furthermore, it argues that systematic ethnographic observations not only can help to understand what matters in early childcare for different persons, but also examine the social processes behind preferences and priorities and how they resonate with social divisions of broader society.